Beyond freedom and dignity - Skinner, B. F. (New York, NY Bantam/Vintage, 1971)
In this profound and profoundly challenging book, the great behaviorist B.F. Skinner, regarded by many as the most influential and controversial living psychologist, author also of the celebrated utopian novel Walden Two, makes his definitive statement about man and society. Insisting that the frightening problems we face in the world today can be solved only by dealing much more effectively with human behavior, Skinner argues that our traditional concepts of freedom and dignity must be sharply revised. They have played an important historical role in man's struggle against many kinds of tyranny, he acknowledges, but they are now responsible for the futile defense of a free and worthy autonomous man; they are perpetuating our use of punishment and are blocking the development of more effective cultural practices. Basing his arguments on the massive results of the experimental analysis of behavior in which he pioneered, he rejects traditional explanations of behavior in terms of states of mind, feelings, and other mental attributes in favor of explanations to be sought in an individual's genetic endowment and personal history. He tells why, instead of promoting freedom and dignity as personal attributes, we should direct our attention to the physical, and social environments in which people live. It is the environment that must be changed rather than man himself if the traditional goals of the struggle for freedom and dignity are to be reached. A technology of behavior able to solve our problems by effectively changing the world in which people live will, in its turn, raise frightening questions. Will men become robots? Or victims? Or merely passive spectators? Who is to design that brave new world of the future? Can we count on his benevolence, or will a technology of behavior necessarily mean a new kind of tyranny? These and many other questions concerning so-called "value judgments" are squarely faced. The book forces us to look afresh at ideals we have taken for granted and to consider the possibility of a scientific approach which, though it may at first seem incompatible with those ideals, will enable us to avoid the destruction toward which we are
Keywords: Human behavior; Free will and determination